TECHNOLOGY ASSESSMENT AND ATTRACTIVE ANALYSIS OF A NEW CONCRETE MODIFIER - Maruti S. Bhosale1,R.M.Mane2 (International Journal of Innovations in Engineering Research and Technology, 2022)
MB, a new concrete modifier containing Silica Fume (FS), has fantastic performance. A government decided to invest to produce this new concrete modifier. Technology assessment (TA), attractiveness analysis (AA), and business modeling are three main phases to study this investment.ApplyingTA andAA helps decisionmakerstomake theirmindbasedontechnological facts and realities of the market. This paper covers the results of phases 1 and 2.At the end, MB is introduced a superior technology and appropriate strategies to enter themarketandacquirethetechnologyareproposed.